THE EFFECT OF PAPAYA SEED EXTRACT ADMINISTRATION THROUGH DRINKING WATER ON THE PERFORMANCE AND IOFDC OF NATIVE CHICKENS - D. N., AYU; DEWI, G. A. M. K.; SUARTA, G. (Majalah Ilmiah Peternakan; Vol 28 No 1 (2025): Vol. 28 No. 1 (2025), 2025)
This study aimed to determine the effect of papaya seed extract administration through drinking water on the performance and income over feed and drink cost of kampung chickens. The research was conducted for 8 weeks at Farm Sesetan, Faculty of Animal Husbandry, Udayana University. A Rancangan Acak Leingkap was used with 4 treatments and 4 replications, with each replication consisting of 5 kampung chickens. The treatments were as fol- lows kampung chickens given drinking water without papaya seed extract (P0), kampung chickens given drinking water with 3% papaya seed extract (P1), kampung chickens given drinking water with 4% papaya seed extract (P2), and kampung chickens given drinking water with 5% papaya seed extract (P3). The results showed that there was no significant increase (P>0.05) in feed consumption, water consumption, final body weight, and weight gain com- pared to P0. However, the FCR values of treatments P2 and P3 showed significant differences (P<0.05) compared to P0 and P1. IOFDC differed significantly (P<0.05), with P2 and P3 having higher values compared to P0. Based on the results, it can be concluded that the administration of 4% and 5% papaya seed extract through drinking water significantly decreased the FCR and increased the IOFDC.